PENERAPAN ALGORITMA MESSAGE DIGEST 5 PADA FILE VIDEO - Hondro, Rivalri Kristianto (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2020)
ABSTRACT The use of video documents as one of the media to convey information is very widely used today. Where is evident in some social networking applications contain a lot of content about information in the form of videos. Paying attention to the security side of the video aims to ensure that the information contained in the video cannot be accessed by people who are not interested. Besides, the security side that must be ensured is maintaining the authentication of data to avoid manipulation actions carried out by people who are not responsible. One of the video security techniques that can ensure the authenticity or authenticity of a video is cryptographic techniques. One cryptographic algorithm that can ensure the authentication of the video is the message digest 5 algorithm. The results obtained from the application of message digest 5 are hash codes that can be used as the values of meters to express the authenticity of the video metadata identity. Keyword: Authentication, Cryptography, Message Digest 5 Algorithm, Video Abstrak Pemanfaatan dokumen video sebagai salah satu media untuk menyampaikan informasi sangat banyak digunakan saat ini. Dimana terbukti dibeberapa aplikasi jejaringan sosial banyak memuat konten tentang informasi dalam bentuk video. Memperhatikan sisi keamanan dari video bertujuan untuk memastikan informasi yang ada pada video tidak dapat diakses oleh orang yang tidak berkepentingan. Selain itu juga sisi keamanan yang harus dipastikan adalah menjaga otentikasi dari sebuah data untuk menghindari tindakan-tindakan manipulasi yang dilakukan oleh orang yang tidak bertanggung jawab. Salah satu teknik keamanan video yang dapat memastikan otentikasi atau keaslian dari sebuah video adalah teknik kriptografi. Salah satu algoritma kriptgrafi yang mampu memastikan otentikasi dari pada video adalah algoritma message digest 5. Hasil yang didapatkan dari penerapan message digest 5 adalah kode hash yang dapat dijadikan sebagai nilai para meter untuk menyatakan keaslian dari identitas meta data file video. Kata Kunci: Otentikasi, Kriptografi, Algoritma Message Digest 5, Video